Medical errors, affected sites, and adverse consequences among patients in the orthopaedic department: Does age matter? - Paicheng Liu; Paicheng Liu; Jianxin Cheng; Yuxuan Yang; Haipeng Zhu (Frontiers Media S.A., 2024)
BackgroundOrthopaedics have become the focus of research on patient safety due to the high incidence of medical errors. Previous studies were based on all orthopaedic patients and rarely conducted empirical analyses from the perspective of age. This study aimed to fill the academic gap in the age variable by comparing medical errors, affected sites, and adverse consequences in orthopaedic patients.MethodsThis retrospective study included 329 litigation claims against orthopaedists using data from China Judgments Online. First, we performed computer crawling and screened 5,237 litigation documents using keywords, including medical errors. Second, 2,536 samples were retained through systematic random sampling, and 549 irrelevant cases were deleted after manual reading. Finally, three clinicians from different medical departments selected 329 incidents related to orthopaedics for further analysis, according to the description of the lawsuits. Three other professional orthopaedists evaluated the patients' ages, affected sites of medical errors, and adverse consequences.ResultsThe greatest number of medical errors was observed in the joints (30.43%) for all orthopaedic patients. However, adult patients (aged 18-60 years) were most susceptible to errors in the extremities (30.42%). A higher rate of complications was associated with a higher rate of morbidity/mortality for the corresponding patients. Medical errors correlated with complications occurred in the following sites: joints (15.38%), extremities (12.50%), spine (16.95%), multiple sites (15.38%), and hands and feet (14.81%). In addition to surgical errors, over 10% of all orthopaedic patients experienced missed diagnoses. The incidence of insufficient adherence to informed consent obligations was 13.5% among adult patients and was much higher in paediatric and older adults patients. When orthopaedic patients suffered from medical technical errors, iatrogenic mortality/morbidity would decrease by 0.3% for one unit increase in age.ConclusionDividing patients into different ages demonstrated diverse results in terms of medical errors and affected sites. Negligence in diagnosis and examination can be fatal factors that endanger safety, and complications may cause morbidity/mortality. When patients suffered from technical errors, age is inversely proportional to mortality/morbidity. Special attention needs to be paid to technical errors in the younger older adults population (60-64 years old), which has inspired implications in promoting aging and public health.